Voluntary Disclosure and Equity Offerings: Reducing Information Asymmetry or Hyping the Stock? - LANG, MARK H.; Lundholm, Russell J. (Contemporary Accounting Research, 2000)
We examine corporate disclosure activity around seasoned equity offerings and its relationship to stock prices. Beginning six months before the offering, our sample issuing firms dramatically increase their disclosure activity, particularly for the categories of disclosure over which firms have the most discretion. The increase is significant after controlling for the firm's current and future earnings performance and tends to be largest for firms with selling shareholders participating in the offering. However, there is no change in the frequency of forward-looking statements prior to the equity offering, something that is expressly discouraged by the securities law. Firms that maintain a consistent level of disclosure experience price increases prior to the offering, and only minor price declines at the offering announcement relative to the control firms, suggesting that disclosure may have reduced the information asymmetry inherent in the offering. Firms that substantially increase their disclosure activity in the six months before the offering also experience price increases prior to the offering relative to the control firms, but suffer much larger price declines at the announcement of their intent to issue equity, suggesting that the disclosure increase may have been used to “hype the stock” and the market may have partially corrected for the earlier price increase. Firms that maintain a consistent disclosure level have no unusual return behavior relative to the control firms subsequent to the announcement, while the firms that “hyped” their stock continue to suffer negative returns, providing further evidence that the increased disclosure activity may have been hype, and suggesting that the hype may have been successful in lowering the firms' cost of equity capital.